PEAR FRUIT STORAGE TECHNOLOGIES BASED ON CHITOSAN PREPARATIONS AND ITS DERIVATIVES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: The study provides information on the use of chitosan. Chitosan is known to have a unique biological activity that can induce resistance to viral diseases in plants, inhibit viral infections in animals and prevent the development of fugue infections in an infected culture of microorganisms. A new environmentally friendly polymer chitosan and its compositions with organic acids, which increase the shelf life of apple fruits by type, and the mechanisms of action of biological products on shelf life are also being investigated.